2021
DOI: 10.1186/s12884-020-03500-y
|View full text |Cite
|
Sign up to set email alerts
|

The views of pregnant women in New Zealand on vaginal seeding: a mixed-methods study

Abstract: Background Vaginal seeding is the administration of maternal vaginal bacteria to babies following birth by caesarean section (CS), intended to mimic the microbial exposure that occurs during vaginal birth. Appropriate development of the infant gut microbiome assists early immune development and might help reduce the risk of certain health conditions later in life, such as obesity and asthma. We aimed to explore the views of pregnant women on this practice. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Neonatal exposure to maternal vaginal fluids immediately after CS birth (more commonly known as ‘vaginal seeding’) is a potential mechanism to foster the development of the gut microbiome. Vaginal seeding has gained traction in recent years [ 37 , 38 ], despite warnings from some healthcare professionals that this procedure poses considerable infection risks to neonates [ 39 , 40 ]. Notably, evidence for the efficacy of this procedure has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal exposure to maternal vaginal fluids immediately after CS birth (more commonly known as ‘vaginal seeding’) is a potential mechanism to foster the development of the gut microbiome. Vaginal seeding has gained traction in recent years [ 37 , 38 ], despite warnings from some healthcare professionals that this procedure poses considerable infection risks to neonates [ 39 , 40 ]. Notably, evidence for the efficacy of this procedure has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been increasing interest in vaginal seeding, only a few published studies have examined its use in humans (Butler et al, 2021). One small pilot study by Dominguez found that the microbiomes of babies born via cesarean section who received vaginal seeding were more similar to those born vaginally in terms of their skin, oral cavity, and anal cavity microbiota.…”
Section: Vaginal Seedingmentioning
confidence: 99%
“…One small pilot study by Dominguez found that the microbiomes of babies born via cesarean section who received vaginal seeding were more similar to those born vaginally in terms of their skin, oral cavity, and anal cavity microbiota. However, since no stool samples were collected, the effect of seeding on the intestinal microbiota remains unclear (Butler et al, 2021).…”
Section: Vaginal Seedingmentioning
confidence: 99%
“…While this area of research will undoubtedly contribute significant insight into postnatal microbiota transplantation procedures and effects on health, this topic has also garnered a growing fascination in public discourse over the last several years. Reflecting a trickle-down effect on social attitudes, a recent study examining attitudes towards vaginal seeding reported that pregnant individuals viewed these procedures as replicating a natural process and may help reduce maternal shame and guilt about undergoing c-section [ 64 ]. This self-reported shame and guilt about undergoing a lifesaving procedure reflects a long cultural history of blaming mothers for negative outcomes in their children, particularly mothers from historically oppressed groups [ 65 ].…”
Section: Influence Of the Prenatal Maternal Microbiome On Neonatal He...mentioning
confidence: 99%